Trends and impacts of e-cigarette use among medical students at a private university in São Paulo, analysis of influencing factors and long-term health implications: A systematic review - de Carvalho, Rodrigo Sousa; Oliveira, Danilo Matos; Oliveira, Andressa Conceição de Maria Melo; Saubier, Telma Aparecida; Batista, Viviane Claudino; Dutra, Luís Gustavo Bogea Moreira; de Oliveira, Guilherme Melo; Machado, Sarah Camila Valesi; Andrade, Romário Ferreira; Jorge, Eduarda Franco; José, Samara da Silva São; Castilho, Rafaella da Matta (Seven Editora, 2024)
This article investigates the perception and use of e-cigarettes among medical students at a private university in São Paulo, exploring the influencing factors and associated long-term consequences. The objective is to carry out a critical synthesis of the available literature on the subject, identifying gaps and suggesting areas for future research. Using a systematic review, recent articles and studies were selected from academic databases such as PubMed, Scielo and Lilacs. The inclusion criteria included studies investigating the use of e-cigarettes among medical students, the factors that influence this use, and the health impacts. The results indicate that the popularity of e-cigarettes among medical students is driven by the perception that they are less harmful than conventional cigarettes, the diversity of flavors, and targeted marketing. However, the short- and long-term adverse health effects are significant, including respiratory problems, cardiovascular problems, and the risk of nicotine dependence. Peer influence, the availability of devices, and the lack of strict regulation all contribute to the increased use of these devices among medical students. The review highlights the need to implement effective educational campaigns and robust public policies to mitigate the risks associated with the use of e-cigarettes among medical students in São Paulo. DOI:https://doi.org/10.56238/sevened2024.016-022